Farmers’ willingness to enter the rural collective commercial construction land market and influencing factors :Based on a survey of 1029 farming households in Jiangsu Province - YE Lifang, ZHANG Xiaodan, ZHANG Yulu, PENG Ziqi, MENG Hao (Ziyuan Kexue)
[Objective] Marketization of collective commercial construction land is a strategic initiative to prioritize agricultural and rural development. After carrying out the “three land” reform pilot in 2015, China launched the second round of pilot work again in 2023 and put forward new requirements, and the associated practices urgently need the support of relevant theoretical research. The willingness of farmers plays an important role in the implementation of land policies, but there had been relatively few studies on farmers’ awareness and willingness to enter the market, for collectively commercial construction land. Therefore, the research conduct a comparative study of farmers’ willingness to enter the market in pilot and non-pilot areas. [Methods] The research group constructed a Theory of Planned Behavior (TPB) model of farmers’ willingness to enter the market from the three dimensions of behavioral attitudes, subjective norms, and perceptions of behavioral control, and conducted research in 13 prefectural-level cities in Jiangsu Province, which is at the forefront of the marketization of collective commercial construction land in the country, to obtain 1029 valid questionnaires from farmers in pilot and non-pilot areas, and analyzed their willingness to enter the market in both pilot and non-pilot areas using the ordered Probit model. The model compared and analyzed the willingness of farmers to enter the market and its influencing factors in pilot and non-pilot areas. [Results] (1) The proportion of farmers willing to enter the market in pilot areas is 95.2%, while the proportion of farmers willing to enter the market in non-pilot areas is 90.5%. (2) Behavioral attitudes had a significant influence on farmers’ willingness to enter the market. Among them, the level of policy comprehension had a positive and significant effect on the willingness to enter the market, while the attachment to land had a significant negative impact in pilot and non-pilot areas and a negative impact (not significant) in pilot areas. Farmers’market entry mode preference had a significant negative impact in pilot areas, while the transaction method had a significant negative effect on their willingness to enter the market in non-pilot areas. (3) The subjective norms had a significant effect on the farmers’willingness to enter the market. The policy promotion had a positive and significant impact in pilot areas, and the village positions had a positive and significant impact in non-pilot areas. (4) The perception of behavioral control had a significant impact on farmers’ willingness to enter the market, with the impact of agricultural land area on farmers’ willingness to enter the market being opposite in pilot and non-pilot areas. [Conclusion] The overall willingness of farmers in Jiangsu Province to enter the market is relatively high. Policy advocacy contributed significantly to farmers’ willingness to enter the market, and farmers’ recognition of the benefits of entering the market would improve their attitudes and behavioral willingness to enter the market. Therefore, this article put forward corresponding policy recommendations from three aspects, including intensifying policy publicity, standardizing the proportion of government benefit allocation, and developing diversified income payment methods.